2019
DOI: 10.1007/s40091-019-00246-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis and experimental testing of ultra-high performance fibre reinforced concrete keyed dry and epoxy joints in precast segmental bridge girders

Abstract: Although ultra-high performance fiber reinforced concrete (UHPFRC) has been used recently as a sustainable construction technique for many precast segmental bridges (PSBs), no exhaustive numerical and experimental studies exist to assess the shear capacity and failure pattern of the joints in these bridges. Hence, to accurately investigate the shear behavior of the joints in UHPFRC precast segmental bridges, a numerical analysis model based on finite-element code was established in this study. Concrete damaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This can be done by carrying out a material calibration for a single element and structure (beal in bending in our case). To study with precision, the shear behavior of joints in segmental bridges prefabricated in ultra performance fiber-reinforced concrete (Gopal et al , 2019) opted for the CDP model. They simulated the inelastic behavior of fiber concrete under compression and traction plan loadings.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done by carrying out a material calibration for a single element and structure (beal in bending in our case). To study with precision, the shear behavior of joints in segmental bridges prefabricated in ultra performance fiber-reinforced concrete (Gopal et al , 2019) opted for the CDP model. They simulated the inelastic behavior of fiber concrete under compression and traction plan loadings.…”
Section: Modelingmentioning
confidence: 99%
“…They simulated the inelastic behavior of fiber concrete under compression and traction plan loadings. Based on the good results of these studies (Tysmans et al , 2015; Singh et al , 2017; Solhmirzaei and Kodur, 2017; Gopal et al , 2019), we adopted the CDP model available in Abaqus and used it to reproduce the behavior of CC and fibers reinforced concretes.…”
Section: Modelingmentioning
confidence: 99%
“…There was no direct relationship between bonding strength and adhesive layer thickness. However, in the subsequent studies, Gopal B A et al [ 26 ] conducted parametric studies on the influence of the number of shear keys, lateral stress, node type, and other factors on the shear capacity of joints. The results showed that the bearing capacity of UHPFRC bond joints increased with the increase of the horizontal pressure (confining pressure) applied to the joints, the number of shear keys, and the thickness of epoxy resin used on the joints.…”
Section: Introductionmentioning
confidence: 99%
“…e experimental results of Smittakor et al [10] showed that steel fiber could improve the shear resistance of concrete keyed joints. Gopal et al [11] found that the shear bearing capacity of ultra-high-performance fiber reinforced concrete (UHPFRC) key joints increased significantly with the number of keys. Kim et al [12] conducted direct shear experiments on the joints of ultra-high-performance concrete (UHPC) and concluded that the failure load gradually increased with the number of keys.…”
Section: Introductionmentioning
confidence: 99%